2022
DOI: 10.1039/d1dt03176g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural characterization, and magnetic property study of {Cr3Ln3}, Ln = Gd and Dy complexes

Abstract: We report a combined computational and experimental study of efficient QTM suppression in {Cr3Dy3} triangle-in-triangle SMMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…The J GdCr exchange value obtained for complex 1 is similar to that for the other reported butterfly {Cr III 2 Gd III 2 } complex ( J GdCr =−0.96 cm −1 ) [9] and also similar to the observed one in a related {Cr III 3 Gd III 3 } complex [23] as well as in a {Cr III 8 Gd III 8 } ring [28] where also the double μ ‐alkoxo/hydroxo‐ μ ‐carboxylate motif is found for the Cr−Gd bridging pathway. To the best of our knowledge these are the only reported examples where J CrGd exchange parameters values are assessed for this type of Cr−Gd bridge.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The J GdCr exchange value obtained for complex 1 is similar to that for the other reported butterfly {Cr III 2 Gd III 2 } complex ( J GdCr =−0.96 cm −1 ) [9] and also similar to the observed one in a related {Cr III 3 Gd III 3 } complex [23] as well as in a {Cr III 8 Gd III 8 } ring [28] where also the double μ ‐alkoxo/hydroxo‐ μ ‐carboxylate motif is found for the Cr−Gd bridging pathway. To the best of our knowledge these are the only reported examples where J CrGd exchange parameters values are assessed for this type of Cr−Gd bridge.…”
Section: Resultssupporting
confidence: 88%
“…In this sense, it is a targeted synthetic approach. A rather similar procedure using N‐methyldiethanolamine instead of triethanolamine gave {Cr III 3 Ln III 3 } systems [23] as product, suggesting that the control of nuclearity in this case is driven by the alcohol‐amine ligand. In contrast, in other related Cr(III)/Ln(III) systems the nuclearity control was driven by lanthanide ion size [24] …”
Section: Resultsmentioning
confidence: 92%
“…Surprisingly, unlike 52a , the Dy III analogue 53b displayed SMM behaviour at zero dc field below 4 K. This example nicely showcased that subtle changes in the peripheral ligand backbone create a major impact in altering the magnetic properties. 76…”
Section: Criii–lniii Heterometallic Complexes Of Varying Nuclearitiesmentioning
confidence: 99%
“…The typical examples are {CrLn 2 }, 67,68 {Cr 2 -Ln 2 }, 69,70 {Cr 2 Ln 3 }, 71,72 {Cr 4 Ln}, 73 {Cr 2 Ln 4 }, 74,75 {Cr 3 Ln 3 }, 76,77 {Cr 4 Ln 4 }, 78–80 {Cr 3 Ln 6 }, 81 {Cr 6 Ln 6 } 82 and {Cr 8 Ln 8 }. 83 All these compounds unveiled interesting magnetic properties, and some even turned out to have excellent SMMs.…”
Section: Introductionmentioning
confidence: 99%
“…This is because 3d ions can impart stronger magnetic coupling and/or magnetic anisotropy, while 4f ions contribute significant single-ion magnetic anisotropy. The seminal work in the field of 3d-4f systems by Gatteschi et al unveiled a fairly strong Cu–Gd ferromagnetic exchange interaction, and finally after two decades, a tetranuclear Cu 2 II Tb 2 III complex has been reported that displayed SMM characteristics for the first time in the class of the 3d-4f system . Thereafter, a large number of SMMs with different nuclearities and topological structures have been reported, particularly those consisting of Cr III , Mn III/IV , Fe II/III , Co II , and Ni II ions. Among the various transition metal ions involved in the construction of 3d-4f complexes, the Co II - or Ni II -containing systems are quite advantageous as in addition to the usual ferromagnetic interaction between these 3d and 4f metal ions, leading to the large ground spin state, they may also contribute anisotropy to the 3d-4f clusters. ,, Consequently, a number of interesting 3d-4f SMMs with Co II or Ni II ions have been reported with varying nuclearity and topology. …”
Section: Introductionmentioning
confidence: 99%